Pengaruh Pergantian CEO terhadap Manajemen Laba dengan Komisaris Independen sebagai Variabel Moderasi - Erliza Miranda Putri; Usep Syaipudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the impact of CEO turnover on earnings management in non-financial companies listed on the Indonesia Stock Exchange (BEI) during the period of 2018–2023, with independent commissioners as a moderating variable. Multiple linear regression is used as the model, and the results show that CEO turnover has a significant negative impact on earnings management, where the new CEO tends to engage in earnings management through Big Bath Accounting to improve future performance. Furthermore, independent commissioners have been proven to significantly moderate the relationship between CEO turnover and earnings management, with a higher proportion of independent commissioners in the board of commissioners weakening the negative effect of CEO turnover on earnings management. Control variables such as leverage, profitability, and company size also have a significant impact on earnings management practices. This study contributes to the development of corporate governance in Indonesia, particularly regarding the role of independent commissioners in controlling earnings management practices. The findings are expected to provide insights for investors and regulators in assessing the risks of financial report manipulation and improving transparency and accountability in companies listed on the stock exchange.